2018
DOI: 10.2147/jpr.s146050
|View full text |Cite
|
Sign up to set email alerts
|

Neck/shoulder function in tension-type headache patients and the effect of strength training

Abstract: IntroductionMuscle pain has been associated with reduced maximal muscle strength, and reduced rate of force development (RFD). Strength training (ST) has shown an effect in not only normalizing muscle function but also reducing neck muscle pain.AimThe aims of this study were to compare muscle function in terms of strength, force steadiness in neck flexion, as well as extension, and rate of RFD of the shoulder in tension-type headache (TTH) patients and healthy controls and to examine the correlation to tendern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…This assumption is based on the presence of motor output changes of the cervical musculature, e.g., reduced neck muscle strength [62], an increased co-activation of the superficial cervical muscles [63], in patients with TTH. In fact, the application of strengthening exercises, ergonomic/posture correction programs and motor control exercise programs have demonstrated to be effective in TTH [64][65][66]. Interestingly, Castien et al found that neck flexor musculature endurance partially mediates the potential effects of manual therapy interventions in TTH [67].…”
Section: Scientific Evidence Of Exercise Interventions For Headachesmentioning
confidence: 99%
“…This assumption is based on the presence of motor output changes of the cervical musculature, e.g., reduced neck muscle strength [62], an increased co-activation of the superficial cervical muscles [63], in patients with TTH. In fact, the application of strengthening exercises, ergonomic/posture correction programs and motor control exercise programs have demonstrated to be effective in TTH [64][65][66]. Interestingly, Castien et al found that neck flexor musculature endurance partially mediates the potential effects of manual therapy interventions in TTH [67].…”
Section: Scientific Evidence Of Exercise Interventions For Headachesmentioning
confidence: 99%
“…As such, Madsen et al reported a 12% decrease in neck extension/flexion strength ratio in the TTH population36 and a 26% difference in extension strength between TTH and healthy subjects 21. In addition, patients with TTH have been found to have significantly lower neck extension force steadiness compared with healthy controls 35. Even though in our study those with severe headache-related disability showed a significantly reduced force production, the TTH group as a whole did not show a significant difference in neck extensor force compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, Madsen et al reported that concomitance of neck tenderness in patients with TTH has a negative influence on force production which could be explained by a modulation of muscle activity aimed at avoiding painful experiences characterised by an increased activity in antagonist muscles and a decreased activity in agonist muscles 35. An imbalance in force production between the neck flexor and extensor muscles has also been considered a potential contributing factor of CTTH development.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Finally, others showed that force steadiness deficits in people with neck, shoulder pain or knee osteoarthritis were apparent only during specific movements and/or during the exertion of high forces. 13 31 32 …”
Section: Introductionmentioning
confidence: 99%